Education, earnings and the labour market - Watson, I (My University, 2011)
This report is a theoretical journey through the landscape of educational qualifications and the earnings attached to them. It is primarily an account of the labour market, and education features in only a subsidiary way. This reflects my own background as a labour market researcher, rather than the relative importance of these two areas. The implications for VET are certainly canvassed, but the problems posed by labour market change are central to this story. While theoretical in scope, the report also includes a section of original econometric modelling using some of the latest survey data available (2009). There are also a number of excursions into other domains, such as the various historical and sociological asides which arise in various parts of the report. These may appear distractions, but it is my contention that unpacking theoretical concepts requires an understanding of the historical and sociological contexts in which those concepts apply. For example, unpacking productivity and earnings requires not only an understanding of their conceptual elements, but also insights into how they have played out in the Australian labour market in recent decades. While the core of the report is the labour market, the theme around which much of the analysis revolves is human capital theory. There are many debates in this field, and I only touch on these briefly. I do not wish to rehearse familiar arguments. I think greater value lies in delving more deeply into the core concepts which human capital theory relies upon, particularly those around productivity and earnings. Pushing these further than they are usually taken is a worthwhile exercise and is justified by the theoretical scope of this report. At the same, however, the report also presents summaries of a number of recent empirical studies on qualifications and earnings in Australia. This section of the report also contains the original econometric analysis mentioned above. Consequently, this report is both theoretical and empirical, and its presentation alternates between a logical sequence of concepts, a summary of some economic modelling, and a more discursive narrative about the recent past. While certain core arguments are presented forcefully, the goal is not polemic but illumination.
Report for Skills Australia
Keywords: Employment -- Labour markets; Education and Training -- Educational level; Income & Finance -- Income (Salary and Wages); Learning, education and training; Income, wealth and finances; Labour market; Employment; Education and Training; Income & Finance; Income (Salary and Wages); Educational level; Labour markets; Learning, education and training; Employment and unemployment; Income, wealth and finances